Proceedings of a symposium on sustainable agriculture. The role of green manure crops in rice farming systems 25-29 May 1987 ([Philippines], 1988)
The book collects papers presented on the symposium on the role of green manure crops in rice farming systems, papers were presented on the present knowledge and practices of green manure utilization in rice-based cropping systems, on the effects on the soil fertility, on the integrated use of forage- and food-legumes in rice-based cropping systems, on germplasm collection and on the production of mung bean and soya bean seed. Recommendations for the research needed and a framework for the research coordination were made
Keywords: Rice,Green manure crops; Fertilizers